Analysis of Radiographic Spinopelvic Parameters in Patients With Degenerative Lumbar Kyphoscoliosis. (9th July 2021) - Ge, Rile; Yang, Peng; Liu, Xin; Wen, Bingtao; Guo, Zhaoqing; Chen, Zhongqiang
Purpose: To analyze the relationships between coronal and sagittal spinopelvic parameters in degenerative lumbar kyphoscoliosis (DLKS). Methods: We enrolled 75 patients with DLKS for a radiographic study between January 2016 and September 2018. Correlations between coronal and sagittal spinopelvic radiographic parameters were analyzed. Then patients were divided into 2 groups: sagittal balanced group (SVA< = 5 cm, 30 patients) and sagittal imbalanced group (SVA >5 cm, 45 patients), and relevant parameters were compared. Results: The Cobb angle and lumbar lordosis of the DLKS patients were 24.87 ± 11.59° and 17.26 ± 12.24°, respectively. The average age was 68 years old (range: 42-82), and the sex ratio was 2.6:1 (female: 54 patients; male: 21 patients). 50 patients (66.7%) located convexity of the curve at left side, while 25 patients (33.3%) at right side. The Cobb angle correlated with LL-TK (r = −0.228, p = 0.049), LL (r = −0.255, p = 0.027) and SS (r = −0.232, p = 0.045). There were significant differences in PI-LL (t = −3.484, P = 0.001), LL-TK (t = 2.354, P = 0.023), PI (t = −3201, P = 0.002) and PT (t = −2.521, P = 0.014) between sagittal balanced and imbalanced group. Conclusions: In degenerative lumbar kyphoscoliosis, there are some correlations between coronal and sagittal spinopelvic parameters. Moreover, PI-LL, LL-TK, PI, PT were significantly different between sagittal balanced and imbalanced DLKS patients.